HUBUNGAN FUNGSI KEPEMIMPINAN KEPALA DESA DENGAN EFEKTIVITAS KERJA APARATUR PEMERINTAH DESA (Suatu Studi Di Kecamatan Langowan Utara Kabupaten Minahasa) - Rewah, Daniel; Lengkong, florence Daicy; Mandey, Jantje (Sam Ratulangi University, 2015)
Abstract: This study aims to: Describe the function of the leadership of the village head and villageofficials effectiveness; and analyze the relationship between the leadership function of the villagehead and village officials work effectiveness in Minahasa District of Northern Langowan. Purposivesample of respondents assigned as many as 80 people were distributed into four (4) of 8 (eight)villages in the districts of North Minahasa Langowan. Members randomly drawn sample consisted of40 people from local government and 40 others are members of BPD, community / religion. Themethods and approach used in this research is descriptive and quantitative approach by applyinganalytical techniques percentage, product moment correlation and simple linear regression. Theresults obtained from this study are: the results of the analysis of frequency table shows that theleadership function village head seen from the dimensions of the initiative and dimensions ofgovernment communications, overall in the category